2012
DOI: 10.1128/aem.06556-11
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Response of Campylobacter jejuni to Trisodium Phosphate

Abstract: The highly alkaline compound trisodium phosphate (TSP) is used as an intervention to reduce the load of Campylobacter on poultry meat in U.S. poultry slaughter plants. The aim of the present study was to investigate the cellular responses of Campylobacter jejuni NCTC11168 when exposed to sublethal concentrations of TSP. Preexposure of C. jejuni to TSP resulted in a significant increase in heat sensitivity, suggesting that a combined heat and TSP treatment may increase reduction of C. jejuni. A microarray analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…This phenomenon was proposed to be attributable to the contribution of RND pumps (666). However, the effect of PA␤N on OM permeability could also provide an alternative explanation, since the PA␤N concentration used, 64 g/ml, was quite high.…”
Section: Campylobacter Sppmentioning
confidence: 81%
“…This phenomenon was proposed to be attributable to the contribution of RND pumps (666). However, the effect of PA␤N on OM permeability could also provide an alternative explanation, since the PA␤N concentration used, 64 g/ml, was quite high.…”
Section: Campylobacter Sppmentioning
confidence: 81%
“…Riedel, Cohn, Stabler, Wren, and Brøndsted (2012) reported that pre‐exposure of C. jejuni to TSP resulted in heat sensitivity and detected genes that were differently expressed after sublethal TSP exposure; however, the authors attributed this effect to alterations in ion transport processes. TSP has surfactant properties, allowing it to remove bacteria not firmly attached to poultry skin or surface fat, thereby facilitating the removal of bacteria by washing.…”
Section: Resultsmentioning
confidence: 99%
“…We identified two virulence-associated genes, ctsE and Cj1587c, that were assigned to a transportation function. The gene ctsE, which encodes a putative type II secretion system E protein and is essential for DNA uptake and natural transformation, was classified as having a Campylobacter transformation function [19]. This protein is an important virulence-associated factor because its encoding gene is similar to several genes responsible for the transport of pilus subunits, toxins, and other exoenzymes [23].…”
Section: Discussionmentioning
confidence: 99%